Arsenic Trioxide Leaching and Scorodite Crystallization in Methanesulfonic Acid. (17th November 2022) - Ahn, Junmo; Wu, Jiajia; Ahn, Jaewoo; Lee, Jaeheon
ABSTRACT: Arsenic, one of the most toxic elements, is a byproduct generated from metallurgical processes of arsenic-containing ores. Arsenic can be formed into an arsenic trioxide as a byproduct during the decopperization in electro-refining process when processing high arsenic-bearing copper minerals. However, arsenic trioxide has a very high arsenic mobility, so it requires to be re-dissolved and immobilized into scorodite (FeAsO4 ▪2H2 O). In this study, methanesulfonic acid (MSA) was tested for both arsenic trioxide leaching and scorodite precipitation. Arsenic trioxide leaching tests showed the arsenic extraction of 80% at 21°C in MSA with H2 O2 as an oxidant within 6 hours. Meanwhile, arsenic precipitation tests were conducted to achieve above 95% arsenic removal within 6 hours by the formation of scorodite at an initial pH of 0.5 and temperature of 80°C. In addition, coarser scorodite particles were formed in higher temperature and lower solution pH. The optimum condition for scorodite crystallization in MSA medium can be suggested to be at 80°C with the initial pH of 0.5.